Monstrous (M)others: From Paranoid to Reparative Readings of Othering through Ascriptions of Monstrosity - Thorsen, Tess Sophie Skadegård; Skadegård, Mira Chandhok (Nordlit, 2019)
The Danish film A Horrible Woman (orig. En frygtelig kvinde, 2017) marked a pattern that can be identified throughout several decades of Danish filmmaking. Examples are found in contemporary films like Antichrist (2009), as well as in earlier Danish films like The Abyss (1910) and Red Horses (1950). In these and other examples, women characters exhibit monstrous behavior that can be construed as a form of othering. Furthermore, othering women and mothers by presenting them as terrible, abnormal, or monstrous in Danish (popular) culture goes well beyond the silver screen. In this article, ‘mother–daughter scholars’ Mira Chandhok Skadegård and Tess Sophie Skadegård Thorsen explore how monstrosity functions as a tool for othering in film and other media, offering both a (generational) and historical view, and a discussion of current constructions of monstrosity, on and off screen, in Denmark. The article argues that monstrosity, as a symbol of power and violence, becomes a particularly oppressive gendered gesture. The authors examine this in a correspondence with one another. In letter form, with shifting analytical positions between mother and daughter, a dialogue emerges between generations on questions of ‘(m)otherhood’ in Danish film and other Danish contexts, transitions of female film characters from passive to aggressive, and the role of monstrosity in othering non-white immigrant ‘(m)others’ in public discourse. Finally, the article argues for a different approach to ‘monstrous othering’. Through a reparative reading, it discusses whether there is empowerment and agency connected to being ascribed monstrosity.